1999
DOI: 10.1029/1998rs900007
|View full text |Cite
|
Sign up to set email alerts
|

Wideband analysis of propagation along radiating cables in tunnels

Abstract: Abstract. This paper describes the main electromagnetic characteristics of a radiating cable installed in a gallery. The emphasis is on the effect of the cable environment on the coherence bandwidth and on the delay spread of the radio channel. The direction of arrival of the waves inside the tunnel has also been deduced from the complex impulse response in order to optimize a method of localization of a mobile moving in the gallery. IntroductionRadiating cables are widely used to ensure radio communications i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
0
6
0
2
Order By: Relevance
“…The distance between each slot being on the same order of magnitude as the wavelength, the cable behaves as a long array of equivalent magnetic dipoles. The radiation of such a cable is described in [8], for example, for an application in a road tunnel and in [9] for a digital communication in mine access galleries. A review of various aspects of EM wave propagation in tunnels can also be found in [10].…”
Section: Introductionmentioning
confidence: 99%
“…The distance between each slot being on the same order of magnitude as the wavelength, the cable behaves as a long array of equivalent magnetic dipoles. The radiation of such a cable is described in [8], for example, for an application in a road tunnel and in [9] for a digital communication in mine access galleries. A review of various aspects of EM wave propagation in tunnels can also be found in [10].…”
Section: Introductionmentioning
confidence: 99%
“…The cable is leaky in the sense that it includes gaps or slots in its outer conductor that allow radio signals to leak into or out of the cable along its entire length. As a result of such signal loss, line amplifiers must be installed at regular intervals to boost the signal back to acceptable levels that results in significant weight and cost increases [10]. However, there is a high probability that the cable can be damaged inside the tunnel, resulting in communication complications in the entire tunnel.…”
Section: Introductionmentioning
confidence: 99%
“…However, the design procedure of leaky‐wave‐based cables is much more complicated than surface‐wave‐based cables. To our knowledge, there is no publication in open literature which has systematically discussed the general design theory of the leaky cables, though the characteristics and application problems of the periodically slotted leaky cables have been studied by many researchers [ Hill and Wait , 1980b; Richmond et al , 1981; Delogne and Deryck , 1980; Gale and Beal , 1980; Liénard and Degauque , 1999], and several new leaky wave cables have already been designed by distributing the slot angles in a triangle function [ Kim et al , 1998]. In our previous work [ Wang and Mei , 2001a], a new method was proposed, in which the field distribution in the cable slots was calculated by FDTD method, and the far field was obtained by integrating the aperture field of the slots together with dyadic Green's function.…”
Section: Introductionmentioning
confidence: 99%